Pemberdayaan Korban Kekerasan Terhadap Anak di Panti Asuhan Ananda Sheva Dharma, Buleleng, Bali - Ni Komang Arini Styawati; Johannes Ibrahim Kosasih; I Ketut Kasta Arya Wijaya; I Wayan Rideng; I Made Mardika; I Nyoman Sumardika (Postgraduated Community Service Journal, 2025)
Violence against children is a form of human rights violation that still occurs frequently in Indonesia and impacts children's physical, psychological, and social development. The Ananda Sheva Dharma Orphanage in Sangsit Village, Sawan District, Buleleng Regency, is a social institution that plays a role in fostering neglected children and victims of violence. However, the orphanage lacks representative media to instill disciplinary values, and both administrators and foster children have limited understanding of child protection laws. This Community Service Program (PKM) aims to empower the orphanage to protect child victims of violence through the creation of disciplinary signs, donations, and legal counseling. The methods used include identifying partner needs, implementing activities, and evaluating outcomes. The results of the activities indicate an increased understanding of child protection laws, strengthened implementation of disciplinary rules, and support for the welfare of foster children. The resulting outputs indicate that the orphanage is increasingly capable of carrying out its child protection and empowerment functions sustainably.